A co-pertinência entre Ser e homem no pensamento de Heidegger: em busca da unidade esquecida. - RAMOS, Daniel Rodrigues (2009)
The together-belongingness (Zusammengehörigkeit) of Be-ing and man is discussed in this dissertation in the style of a Phenomenological reflection the together-belongingness (Zusammengehörigkeit) of Be-ing and man. It treats of a concept which appears explicitily in the phenomenological thought of Martin Heidegger, especially, beginning in the 30s, when he questioned the meaning of Truth according to the history of Be-ing, that is, as enowning (Ereignis). The reflection, however, begins with the presupposition together-belongingness is a notion present in the thought of Heidegger from the outset of the fundamental-ontological development of the question of Be-ing, represented principally by the primary work of 1927, Sein und Zeit. For this reason, the reflection begins discussing the unity of the thought itinerary of Heidegger, showing that the reversal of the thinking (Kehre) of the 30s is responsible for the transformation which establishes the same question of Be-ing in a more originating extent than that of Sein und Zeit. Admitting from the beginning that together-belongingness translates the mutual reference between Be-ing and man, coming from the primordial unity, in dependence upon which both bring about historically their essence, and not a secondary and posterior relation between two self-subsisting poles, the discussion proceeds determining the structures of human existence, by which together-belongingness is considered in the different levels of elaboration of the question of Be-ing. Consequently, the central thrust of the dissertation is summarized in limiting the spatial-temporal ambience of the common reference. In the first place, attention is given to the analyses of the comprehension-interpretation project of human existence and language, according to Sein und Zeit. Then, according to Beiträge zur Philosophie, the same ambience is limited taking into consideration the grounding of Da-sein as the intermediary dimension between man and Be-ing, it being the instance of supportability of happening of Truth. Finally, the projection of human existence is revealed as the leap of Be-ing, in such a manner that movement of realization of the essence of Be-ing is shown as being the same as the consummation of the historical existence of men. Thus, the coming about of the Truth, by which Be-ing is experienced as abysmal grounding, is coordinated with the historical coming about of human existence, granting it, in virtue of the depth of its grounding, a unitary movement of revealing and of hiding the mystery of Be-ing. Being that this coordination is the manifestation of the originating space and time, human existence appears as the establishment of the space-time dimension of the abyss of Being, always in agreement with an historical possibility. In this way, the together-belongingness appears as an historical sending-forth, in the form of a questioning which Be-ing directs to man, but which is consumed in the measure which man responds, or as it may be, assumes the responsibility for the destiny of his existence according to the appeals of Be-ing. Thus, thought, understood as a human faculty during all of the history of metaphysics, is reduced to its essence: that by which man corresponds to the historical appeals of Be-ing. To think consumes the intimate reference of man to Be-ing and, therefore, is the privileged manner of placing in operation human existence in union with Be-ing. By means of thought, therefore, man has understood himself separated from and in front of Be-ing. For that reason, the reflection of this dissertation is a path in search of the forgotten unity between man and Be-ing.